Towards a feasible model for shared decision making: focus group study with general practice registrars - Elwyn, Glyn (British Medical Journal, 1999)
OBJECTIVES: To explore the views of general practice registrars about involving patients in decisions and to assess the feasibility of using the shared decision making model by means of simulated general practice consultations. DESIGN: Qualitative study based on focus group interviews. SETTING: General practice vocational training schemes in south Wales. PARTICIPANTS: 39 general practice registrars and eight course organisers (acting as observers) attended four sessions; three simulated patients attended each time. METHOD: After an introduction to the principles and suggested stages of shared decision making the registrars conducted and observed a series of consultations about choices of treatment with simulated patients using verbal, numerical, and graphical data formats. Reactions were elicited by using focus group interviews after each consultation and content analysis undertaken. RESULTS: Registrars in general practice report not being trained in the skills required to involve patients in clinical decisions. They had a wide range of opinions about “involving patients in decisions,” ranging from protective paternalism (“doctor knows best”), through enlightened self interest (lightening the load), to the potential rewards of a more egalitarian relationship with patients. The work points to three contextual precursors for the process: the availability of reliable information, appropriate timing of the decision making process, and the readiness of patients to accept an active role in their own management. CONCLUSIONS: Sharing decisions entails sharing the uncertainties about the outcomes of medical processes and involves exposing the fact that data are often unavailable or not known; this can cause anxiety to both patient and clinician. Movement towards further patient involvement will depend on both the skills and the attitudes of professionals, and this work shows the steps that need to be taken if further progress is to be made in this direction.